2022
DOI: 10.1017/s002237782200068x
|View full text |Cite
|
Sign up to set email alerts
|

Theory of gradient drift instabilities in low-temperature, partially magnetised plasmas

Abstract: A fluid dispersion theory in partially magnetised plasmas is analysed to examine the conditions under which large-wavelength modes develop in Penning-type configurations, that is, where an electric field is imposed perpendicular to a homogeneous magnetic field. The fluid dispersion relation assuming a slab geometry shows that two types of low-frequency, gradient drift instabilities occur in the direction of the $\boldsymbol {E} \times \boldsymbol {B}$ and diamagnetic drifts. One typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…other typical E × B plasmas, such as Hall thrusters [9][10][11][12][13] and Penning discharges [14][15][16][17]. The spoke significantly affects the dynamics of electrons and ions and its fundamental understanding is hereby of importance in the operation and control of these E × B plasma based applications [15,[18][19][20][21][22][23][24][25][26][27]. In magnetrons, the spoke refers to a locally enhanced ionization zone rotating in the azimuthal (E × B) direction above the erosion area (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…other typical E × B plasmas, such as Hall thrusters [9][10][11][12][13] and Penning discharges [14][15][16][17]. The spoke significantly affects the dynamics of electrons and ions and its fundamental understanding is hereby of importance in the operation and control of these E × B plasma based applications [15,[18][19][20][21][22][23][24][25][26][27]. In magnetrons, the spoke refers to a locally enhanced ionization zone rotating in the azimuthal (E × B) direction above the erosion area (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical works (in particular, those related to Hall thrusters [15,33,34]) suggested that a spoke is originated from the drift instability driven by gradients of potential and density. Various theoretical modifications of the gradient drift instability (GDI) were developed, taking into account a variety of effects, such as the magnetic field gradient, inertia, collisions, ion beam and ionization [23,[25][26][27]35]. In recent years, the evidence of GDI being the origin of the spoke was identified by PIC/MCC simulations in planar magnetrons [19], cylindrical magnetrons [18,22,36] and Penning-type discharges [37].…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical work [39] tied to the current study revisited these conditions, re-deriving the fluid dispersion relation for this regime. Assuming the equilibrium electric field and plasma density gradient are in the radial (x) direction, with no variation in the azimuthal (y) direction, with an axial (z) constant, uniform magnetic field, the fluid dispersion relation for a partially magnetized plasma is given by [17]:…”
Section: Rotating Spokes Instabilitymentioning
confidence: 99%